Stroke Prevention in Pregnancy and Postpartum in Patients With Patent Foramen Ovale - Grace B. Russo, MD; Stephanie E. Purisch, MD; Malamo E. Countouris, MD, MS; Lynn M. Yee, MD, MPH; Imo J. Akpan, MD; Robert J. Sommer, MD; Eliza C. Miller, MD, MS (JACC: Advances)
Pregnancy and patent foramen ovale (PFO) are both stroke risk factors in young people. There are currently no guidelines for mitigating PFO-related stroke risk during pregnancy. We summarize the pathophysiology of PFO-related stroke and offer our approaches to primary and secondary stroke prevention for pregnant patients with PFO. We present 5 clinical scenarios: incidentally identified PFO in a pregnant patient without a stroke history; considerations for PFO screening and primary stroke prevention in select patients at unusually high risk of stroke in pregnancy; planning for pregnancy after a PFO-related stroke; PFO-related stroke occurring in pregnancy; and pregnancy planning for a patient with PFO identified after a transient neurological episode of unclear cause. Through these scenarios, we highlight the unique treatment considerations and challenges of primary and secondary PFO-related stroke prevention during this high-risk period. Collaboration between neurology, cardiology, and maternal-fetal medicine is integral for the successful management of these patients.